2010
DOI: 10.5004/dwt.2010.1093
|View full text |Cite
|
Sign up to set email alerts
|

Towards implementation of reverse electrodialysis for power generation from salinity gradients

Abstract: ab s t r ac tReverse electrodialysis is a conversion technique to obtain electricity from salinity gradients. Over the past few years, the performance of reverse electrodialysis on laboratory scale has improved considerably. In this paper, we discuss the challenges we are still facing concerning the economic and technological feasibility and the developing path of reverse electrodialysis. We focus on the following issues: (i) the development of low-cost membranes, (ii) pre-treatment in relation to stack design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(139 citation statements)
references
References 19 publications
2
136
0
1
Order By: Relevance
“…The pretreatment system is based on a setup suggested by Post et al [17]. It consists of coarse mediafiltration in the form of two rotating drum filters, with light chlorination (1 ppm).…”
Section: Model For Pretreatment System Pumpingmentioning
confidence: 99%
See 3 more Smart Citations
“…The pretreatment system is based on a setup suggested by Post et al [17]. It consists of coarse mediafiltration in the form of two rotating drum filters, with light chlorination (1 ppm).…”
Section: Model For Pretreatment System Pumpingmentioning
confidence: 99%
“…We assume a plant life of 20 years (Γ in periods) and an annualized cost of capital r of 6% [17]. The net present value consists of a capital contribution for the RED stack and a capital contribution for the pretreatment system.…”
Section: Model For System Costmentioning
confidence: 99%
See 2 more Smart Citations
“…The power generated is termed as blue energy or salinity gradient power. The total global potential of blue energy has been estimated to be about 1.4-2.6 TW out of which ~980 GW is extractable depending on the technology applied [25]. It has been demonstrated that salinity gradient energy is able to fulfil 20% of the current global energy demand.…”
Section: Energy Production In Desalination Sectormentioning
confidence: 99%